The effect of frying frequency on acid value and peroxides in various types of oil - Rahma Laelia; Pramudya Kurnia (Ilmu Gizi Indonesia, 2019)
Background: People often store frying oil that will be reused or used repeatedly for several times, especially in salted fish frying. Cooking oil that has been used repeatedly with high temperatures or contact with water and oxygen will produce acid and peroxide values. This is due to the oxidation and hydrolysis processes causing oil damage. Objective: To identify the effect of frying frequency on the acid and peroxides value in various types of oil. Methods: This research was an experiment with salted fish frying based on a completely randomized design using three treatments (first, second, and the third frying processed) with three different types of oil, that were coconut oil, palm oil, and corn oil. Acids and peroxides values were analyzed using One Way Anova test continued with Duncan Multiple Range Test (DMRT) test. Results: Acid value in the three types of oil was still within the limits of the standards value 0.6 mg KOH/g based on SNI 3741: 2013 and free fatty acid 0.3% based on SNI 7709:2012. After first until third frying, peroxide value of coconut oil was still within the standard limit, whereas in palm oil and corn oil, after second frying were exceeded of the standard limit based on SNI which have maximal value 10 mek O2/kg. Conclusion: Frying frequency were affected by acid and peroxides values of coconut oil, palm oil, as well as corn oil.